Modern approaches to surgical management of endometrioma. (August 2019) - Gordts, S.; Campo, R.
Abstract: Formation of the ovarian endometrioma consists of implantation, invagination of the ovarian cortex, and adhesion formation. Progression is characterized by repeated injury and repair with degenerative changes. Already with a partially deprived ovarian reserve, resulting from the disease, surgical treatment carries a potential risk of further follicular deprivation. Surgery should therefore be performed with microsurgical precision by experienced hands. Early treatment can possibly prevent further progression. The adverse impact on ovarian reserve of the ablative approach has to be balanced against a lower recurrence rate of a cystectomy. Adapted surgical approaches like a two-step approach or a combination of excisional and ablative surgery has to be considered in case of a large endometrioma. Further studies on the possibility and advantages of sclerotherapy are warranted. Fertility preservation by cryopreservation of ovarian cortex should be part of the informed consent with the patient. Highlights: Ovarian endometrioma is formed through invagination of the ovarian cortex and is an extra-ovarian cyst. Endometrioma by itself has a negative impact on the ovarian reserve by ReTIAR and fibrosis. Each surgical procedure, ablative or excisional, carries the risk of further impairment of the ovarian reserve. The possibility of freezing the ovarian tissue should be discussed with the patient in cases of severe endometriosis.